Design and energy flexibility analysis for building integrated photovoltaics-heat pump combinations in a house. (August 2022) - Gaucher-Loksts, Erin; Athienitis, Andreas; Ouf, Mohamed
Abstract: This paper considers three configurations of air source heat pumps and building-integrated photovoltaic (BIPV) systems in a solar house. This study evaluates energy efficiency and flexibility when interacting with a smart grid. The reference case is a 5 kW BIPV system on the roof with a separate air-source heat pump water heater (HPWH). In the two more novel options we have: first, a 5 kW BIPV/thermal (BIPV/T) roof system where the heated air from the BIPV/T system is ducted to the air source of the HPWH, which also contains integrated thermal storage (hot water); in the second case we have an attached solarium with a 5 kW semi-transparent photovoltaic façade, with the solar heated air in the solarium connected to the air source of the HPWH with integrated water thermal storage. The three cases are modelled with an explicit finite difference thermal network model, and energy performance is determined and compared over a typical heating season in Montreal, Canada. The energy flexibility potential of the options is compared for different scenarios, such as heating the thermal water storage during the daytime (e.g. using the solar heat in the novel options) and using it for space heating during the time that the grid is under stress (and may have price incentives). Results show that the second novel case utilizing the solarium air as the source of the heat pump resulted in an over 80% energy use reduction relative to the reference. In comparison, the BIPV/T configuration had around 20% reduction compared to the reference case. The tank volume and solarium size had the highest impact on the flexibility of the system. Optimal sizes for the tank volume were typically between 300 and 600 L for the house with a floor area of 116 m 2 . Highlights: Analyzed BIPV/T scenarios using solar heat to supply heated air to a heat pump. Compared the energy and flexibility of a ducted BIPV/T and a solar heated solarium. Novel passive solar STPV covered solarium had lowest energy consumption. Maximized energy flexibility using a parametric analysis to size key components. Integrated thermal storage had highest impact on maximizing energy flexibility.